Identifying Victims of Human Trafficking at Hotspots by Focusing on People Smuggled to Europe - Ventrella, Matilde (Social Inclusion, 2017)
Research has shown that smuggling of migrants is associated with human trafficking. Hence, victims of human trafficking amongst smuggled migrants should be identified by EU Member States at hotspots established by the European Commission, to overcome the migrant and refugee crisis. Identified victims should be given a visa and a programme of protection to escape their traffickers. In order to achieve these objectives, research suggests that EU law on migrant smuggling should be amended and the Temporary Protection Directive should be applied to smuggled persons when there is an indication that they may be victims of human trafficking. This approach should be adopted by the EASO in cooperation with police forces investigating smuggling and trafficking at hotspots.